2019
DOI: 10.1002/jctb.6209
|View full text |Cite
|
Sign up to set email alerts
|

How Candida antarctica lipase B can be activated in natural deep eutectic solvents: experimental and molecular dynamics studies

Abstract: BACKGROUND: Natural deep eutectic solvents (NADESs), a class of green solvents which completely accords to 12 principles of green chemistry, have proven to have great potential applications in enzymatic reactions. Despite strong interest, the role of NADESs in these processes, and the molecular interaction between enzymes and NADESs, still remain ambiguous. In the present study, the stability and activity of Candida Antarctica lipase B (CALB) were studied, and the mechanism by which CALB was activated in NADES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…As shown in Figure S3 (see the Supporting Information), there was no peak can be found in the range of 0.35 nm around CALB catalytic triad, which indicated that hydrogen-bonding can hardly be formed between CALB catalytic triad and 3c-NADESs. In this context, we can conclude that CALB catalytic triad may not involve in the synergistic effect with 3c-NADESs, which is consist with the results of our previous study in traditional NADESs . Similarly, the large and medium substrate binding pockets were not involved in synergistic effect process (Figure S4A, B, see the Supporting Information).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As shown in Figure S3 (see the Supporting Information), there was no peak can be found in the range of 0.35 nm around CALB catalytic triad, which indicated that hydrogen-bonding can hardly be formed between CALB catalytic triad and 3c-NADESs. In this context, we can conclude that CALB catalytic triad may not involve in the synergistic effect with 3c-NADESs, which is consist with the results of our previous study in traditional NADESs . Similarly, the large and medium substrate binding pockets were not involved in synergistic effect process (Figure S4A, B, see the Supporting Information).…”
Section: Resultssupporting
confidence: 87%
“…However, the mechanism of the synergistic effect between 3c-NADESs and CALB still remains ambiguous. Inspired by previous studies of our group, , we proposed that molecular interactions between 3c-NADESs and CALB/substrates may play a key role in these processes. To further explore it, the molecular interaction between CALB and Mg-CGly3 was investigated by molecular dynamics study (MD).…”
Section: Resultsmentioning
confidence: 88%
“…As mentioned previously [20], the esterification of glycerol and ibuprofen drives the free enzyme preparation (Lipozyme CALB L), which proceeds in a biphasic solid-liquid system at temperatures lower than 70 • C and in a biphasic liquid-liquid system at temperatures higher than that value; even at 80 • C, there is no apparent deactivation, and a ibuprofen conversion higher than 90% is achieved in 5 h. This stability can be explained in terms of the preferential hydration of the enzyme and minimal molecular contact with glycerol, thus increasing the enzyme rigidity and its stability [54]. The stabilizing effect of glycerol is even more evident in the formulation and use of deep eutectic solvents (DEPs) based on this polyol for lipase-driven reactions [55]. As regards the effect of the solid support of Novozym ® 435 on the stability of the lipase, Lewatit ® VP OC 1600 resin seems to be amphiphilic, so it adsorbs (and absorbs) hydrophobic components in hydrophilic environments and, on the contrary, hydrophilic compounds-such as glycerol-in hydrophobic environments such as oils in the biodiesel process [23].…”
Section: Kinetic Modellingmentioning
confidence: 99%
“…However, while the CALB@SBA-15 was incubated in three solvents at 60 for 8 h, the position of the λ max of was almost fixed Fig. S1B , which indicated that there was no significant change in the secondary structure of CALB 38 . A slight increase in I max over time was observed when RML@SBA-15 incubated in phosphate buffer, and no much difference was observed when it incubated in tert-pentanol and acetonitrile Fig.…”
Section: Fluorescence Analysismentioning
confidence: 95%